2016
DOI: 10.1084/jem.20150894
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 amplifies an innate immune response in the degenerating retina

Abstract: Xi et al. demonstrate that IL-33 is a key regulator of retinal inflammation and degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
93
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 52 publications
(72 reference statements)
9
93
0
Order By: Relevance
“…IL-33 is unique as it is active without caspase-1 cleavage and does not require inflammasome activation for secretion and bioactivity. 109 IL-33 triggers an inflammatory response, recruiting monocytes, contributing to photoreceptor loss in a photoxic retinal model of degeneration 110 and infers a pathogenic role of endogenous IL-33 and an a priori for neutralising IL-33 to reduce myeloid cell accumulation as a possible intervention. However, as with IL-18, and in consideration of the emerging role of IL-33 in inflammatory disorders 111,112 and in the absence of progressive cell death, IL-33 regulates tissue responses.…”
Section: Macrophage Conditioning Angiogenesis and Tissue Viabilitymentioning
confidence: 97%
“…IL-33 is unique as it is active without caspase-1 cleavage and does not require inflammasome activation for secretion and bioactivity. 109 IL-33 triggers an inflammatory response, recruiting monocytes, contributing to photoreceptor loss in a photoxic retinal model of degeneration 110 and infers a pathogenic role of endogenous IL-33 and an a priori for neutralising IL-33 to reduce myeloid cell accumulation as a possible intervention. However, as with IL-18, and in consideration of the emerging role of IL-33 in inflammatory disorders 111,112 and in the absence of progressive cell death, IL-33 regulates tissue responses.…”
Section: Macrophage Conditioning Angiogenesis and Tissue Viabilitymentioning
confidence: 97%
“…(Hudson et al, 2008). Further studies have confirmed that IL-33 is a critical inducer of chemokines in various CNS injury models (Gadani et al, 2015b;Xi et al, 2016), and it is likely affecting both astrocytes and microglia (Gadani et al, 2015b). By RT-PCR ST2 mRNA is highest on microglia at baseline, but interestingly is downregulated by microglia and upregulated by astrocytes after injury (Gadani et al, 2015b).…”
Section: Cellular Expression and Effector Functions Of Il-33 In The Cnsmentioning
confidence: 89%
“…Another recent study addressed IL-33 expression in the retina, finding it expressed in both mouse and human vimentin + Müller glia (Xi et al, 2016). In analysis of retinas from human macular degeneration patients, they also demonstrated upregulation in the diseased tissue relative to healthy controls (Xi et al, 2016).…”
Section: Cellular Expression and Effector Functions Of Il-33 In The Cnsmentioning
confidence: 99%
See 2 more Smart Citations